Juridical Analysis of MSME Trademark Holders Based on Law No. 20 of 2016 Concerning Brand Rights and Geographical Indications - Torong, Eddy Ramon; Sulistiyono, Adi (MultiTech Publisher, 2024)
The legal protection given to trademark certificate holders is that the trademark is valid for 10 years and the only registered trademark owner has the rights to the trademark and cannot be changed without the trademark owner's permission. Law enforcement provided by the Trademark and Geographical Indications Law is criminal and civil. There are other alternatives, namely through arbitration and alternative dispute resolution with the concept of a win-win solution.